Tinjauan Atas Perlakuan Akuntansi Aset Tetap Berdasarkan PSAK Nomor 16 Pada Yayasan Karunia Insani Kabupaten Musi Rawas - Miki Indika; Suharto; Yayuk Marliza; Rian Oktavianie; Guwito Manalu (Universitas Indo Global Mandiri, 2023)
The formulation of the problem in this study is how to treat fixed assets accounting based on PSAK No. 16 on the IPWL of the Karunian Insani Foundation, Musi Rawas Regency. The purpose of this study is to apply fixed asset accounting records based on PSAK No. 16 on the IPWL of the Karunia Insani Foundation, Musi Rawas Regency. This research includes qualitative research. The data used are primary data and secondary data obtained from the research object. The data analysis technique used is descriptive analysis. Data analysis used is qualitative analysis. Data collection methods used are observation, interviews and analysis of related documents. The results of the study are that fixed assets in the IPWL of the Karunia Insani Foundation, Musi Rawas Regency, are classified based on their nature and use. Fixed assets in the IPWL of the Karunia Insani Foundation, Musi Rawas Regency, are measured using the cost model method. Fixed assets in the IPWL of the Karunia Insani Foundation, Musi Rawas Regency, are recognized if they provide future economic benefits. Fixed assets at IPWL Yayasan Karunia Insani Musi Rawas Regency are depreciated using the straight-line method. The recognition of fixed assets in the IPWL of the Karunia Insani Foundation, Musi Rawas Regency, is terminated if the foundation disposes of its fixed assets, such as selling, renting or donating its fixed assets. Fixed assets in the IPWL of the Karunia Insani Foundation, Musi Rawas Regency, are disclosed in the balance sheet report at the end of the period.